Multilobular tumor of the zygomatic bone in a dog - Leonardi, L. (Open Vet J, 2014)
Multilobular tumor of bone (MTB) (also known as Multilobular Osteochondrosarcoma) is an uncommon bone tumor frequently located on the skull of dogs, rarely on the ribs or pelvis. These neoplasms are slow growing, locally invasive, and have the potential to compress and invade the brain. A 10-year-old mixed breed dog was presented with a history of approximately 4 months of progressive growth of a left zygomatic mass. Radiographic investigation revealed a finely granular or stippled non homogeneous radiopaque mass involving the zygomatic arch. After surgery, grossly the neoplasm consisted of multiple, variably sized, grayish-white to yellow nodules separated by collagenous septa of different thickness. Histologically, the tumor was characterized by the presence of multiple lobules containing osteoid and cartilage, separated by a net of fibrous septae. This neoplastic pattern was consistent with a typical multilobular tumor of bone and based on clinical, radiographical, gross and light microscopic findings the definitive diagnosis was made. While reviewing veterinary literature only few cases of MTB were found in dogs.